(untitled) (International relations and international law Journal, 2018)
Geopolitical ascendancy of China as a growing superpower entails to the development of new tendencies in the area of the international security. Chinese policy on sustaining of the energy security and active search of various crudes led to the development not only a transport and logistical strategy, but also to the shifts within strategic environment, especially in area of the India Ocean. Chinese SLOCs (Sea Lines of Communication) in the contemporary period play a crucial role under shaping and development of tendencies in the sphere of regional security. The theme and nature itself of Chinese SLOCs have a complex character and cover such areas like a transportation and logistics, foreign policy and strategy, development of military forces and PLAN capabilities. Key words: logistics and transportation, ports, tankers, PLAN (People`s Liberation Army Navy), strategy, energy.